Review of DSN-MUI Fatwa No. 177/DSN-MUI/II/2018 against the Practice of Paying Products on Credit Using the Shopee PayLater Payment Feature on the Shopee Application - Yoyok Prasetyo; Neneng Fatimah (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2022)
This study aims to find out to practice credit payments using the SPayLater feature in the Shopee application and the suitability of loan funds through the SPayLater feature is based on the DSN-MUI fatwa No.177/DSN-MUI/II/2018 concerning Information Technology-Based Financing Services Based on Sharia Principles. This research was conducted using a descriptive method, which describes specifically the practice of product payments using the SPayLater feature and conformity analysis based on sharia. The results of this study conclude that the use of SPayLater can be done after activation. As for the practice, select the item you want to buy then, click the payment method and select SPayLater, click long payment then confirm, click make the order and enter the Shopeepay PIN. Analysis of the suitability of the DSN-MUI fatwa No. 177/DSNMUI/ II/2018 on loan funds in the form of electronic money in the SPayLater feature there are things in practice that are not in accordance with sharia principles, in which there is an additional fee of minimum installments of 2-95% of the total payment and there are late fees of 5 percent of the total invoices that are due.